Comparative analysis of beet cossettes extraction of different profiles on the industrial extractors - Lulka, Alexander; Liulka, Dmytro; Mironchuk, Valeriy; Bulah, Eugen (My University, 2015)
The process extraction of sucrose conducted from the beet cossettes of different cross-sections. Quality and mechanical characteristics, sucrose loss in pulp, raw juice quality and energy cost depends on the profile shape beet cossettes.
Keywords: beet; extraction; cross-section; cutting; свекла; стружка; резание; єкстрагирование; буряк; стружка; різання; екстрагування; кафедра готельно-ресторанної справи; кафедра технологічного обладнання та комп’ютерних технологій проектування